ADVANCEMENTS IN RENEWABLE ENERGY: A SUSTAINABLE SOLUTION FOR GLOBAL ENERGY DEMANDS - Thakur, Neha; Singh, Bikram; Kumar, Dr. Pankaj (UIR PRESS, 2025)
Energy is the ability to perform work, and in today's world, the need for sustainable energy solutions is more crucial than ever. Renewable energy sources, such as solar, wind, and hydro, offer an eco-friendly alternative to conventional fossil fuels. These sources not only help conserve energy but also contribute to a cleaner environment by reducing dependence on non-renewable resources. Over the past few decades, environmental challenges have intensified, making the adoption of renewable energy technologies more necessary than ever. With the global population rising, energy consumption continues to increase, highlighting the urgent need for alternative energy solutions. This study explores the role of different renewable energy sources and how their adoption evolves with a country's economic growth, measured by real GDP per capita. India, in particular, has emerged as the fourth most attractive renewable energy market globally. The Indian government has been actively promoting sustainable energy initiatives, launching large-scale projects to accelerate the shift toward cleaner energy. The relationship between renewable energy and sustainable development, along with future opportunities in this field, is discussed in detail. The findings suggest that factors such as renewable energy production, energy efficiency, economic growth, and carbon emissions significantly influence renewable energy consumption. To further promote clean energy adoption, the study recommends increased investment in renewable energy production, improvements in energy efficiency, and advancements in green technologies.